Ultrafast electronic relaxation dynamics of atomically thin MoS₂ is accelerated by wrinkling - Xu, Ce (2023)
Strain engineering is an attractive approach for tuning the local optoelectronic properties of transition metal dichalcogenides (TMDs). While strain has been shown to affect the nanosecond carrier recombination dynamics of TMDs, its influence on the sub-picosecond electronic relaxation dynamics is still unexplored. Here, we employ a combination of time-resolved photoemission electron microscopy (TR-PEEM) and nonadiabatic ab initio molecular dynamics (NAMD) to investigate the ultrafast dynamics of wrinkled multilayer (ML) MoS2 comprising 17 layers. Following 2.41 eV photoexcitation, electronic relaxation at the Γ valley occurs with a time constant of 97 ± 2 fs for wrinkled ML-MoS2 and 120 ± 2 fs for flat ML-MoS2. NAMD shows that wrinkling permits larger amplitude motions of MoS2 layers, relaxes electron-phonon coupling selection rules, perturbs chemical bonding, and increases the electronic density of states. As a result, the nonadiabatic coupling grows and electronic relaxation becomes faster compared to flat ML-MoS2. Our study suggests that the sub-picosecond electronic relaxation dynamics of TMDs is amenable to strain engineering and that applications which require long-lived hot carriers, such as hot-electron-driven light harvesting and photocatalysis, should employ wrinkle-free TMDs.